PEMANFAATAN LIMBAH SEKAM MENJADI PRODUK ARANG SEKAM UNTUK MENINGKATKAN NILAI JUAL DI KELURAHAN KIARA, KOTA SERANG, BANTEN - Asep Rafiudin; Abdurrohman; Nanang Kosim; Nursifa Maharani; Siskah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Kiara Village, located in Walantaka Sub-district, Serang City, is an agrarian area where most residents work as rice farmers. Rice milling in this area generates a substantial amount of husk waste, approximately 25% of grain weight, which has largely accumulated and disrupted the environment due to its slow natural decomposition. This article documents and analyzes the transformation of husk waste into a branded rice-husk charcoal product, RASEKAR (Arang Sekam Kiara), as an effort to increase economic value for the local community. The activity was conducted in Kampung Prisein, Kiara Village, on 13 and 26 July 2026, using a qualitative descriptive case-study approach, with data gathered through participatory observation, hands-on practice, and field documentation. Results show that rice husk, containing up to 16.98% silica along with carbon, hydrogen, and oxygen, was successfully processed into husk charcoal that functions as a planting medium, loosens soil, regulates soil pH within the 6.5 to 7 range, and retains moisture. Further analysis indicates that packaging and branding strategy under the RASEKAR label was a determining factor in increasing the market appeal of a product that previously had no economic value. The main constraint identified was the limited combustion technology, which produced excessive smoke. This study recommends upgrading combustion equipment and expanding education to other hamlets in Kiara Village so that the program's benefits are more evenly distributed.